The Effectiveness of Port-City Policies A Comparative Approach - Merk, Olaf (OECD Regional Development Working Papers, 2013)
The relation between ports and their cities have evolved: it is no longer evident that well-functioning ports have automatically a net positive impact on the port-city. There are various trajectories and many ports and port-cities attempt to stimulate port-city development by a range of public policies. Yet, little is known about effectiveness of policies to promote performance of ports and port-cities. This paper aims at filling this gap, by assessing the effectiveness of port-city policies, within various policy areas including port development, port-city economic development, transportation, environment, research and development, spatial development and communication. This is done via a principal component analysis (PCA), based on a database constructed for the purpose of this paper with outcome variables and scores of policies for a set of 27 large world port-cities, that makes it possible to identify policies that are associated with effective policy outcomes and show patterns of related policy outcomes and policies